2017
DOI: 10.1063/1.4999562
|View full text |Cite
|
Sign up to set email alerts
|

Study of surface modes on a vibrating electrowetting liquid lens

Abstract: The increased usage of liquid lenses motivates us to investigate surface waves on the liquid's surface. During fast focal switching, the surface waves decrease the imaging quality. We propose a model that describes the surface modes appearing on a liquid lens and predicts the resonance frequencies. The effects of those surface modes on a laser beam are simulated using Fresnel propagation, and the model is verified experimentally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Compared with natural frequencies of four modes obtained accurately by Strauch M et al, [11] where they observed all the frequencies except 17.95 Hz of mode (1,1) and 209.25 Hz of mode (0,3), the frequencies f 1 -f 4 of the rest four modes have a good match with our analysis and the error is no more than 4.90%, as shown in Table 1.…”
Section: Comparison With Experimentssupporting
confidence: 86%
See 1 more Smart Citation
“…Compared with natural frequencies of four modes obtained accurately by Strauch M et al, [11] where they observed all the frequencies except 17.95 Hz of mode (1,1) and 209.25 Hz of mode (0,3), the frequencies f 1 -f 4 of the rest four modes have a good match with our analysis and the error is no more than 4.90%, as shown in Table 1.…”
Section: Comparison With Experimentssupporting
confidence: 86%
“…Since electrowetting liquid lens was innovated, it has been received increased attention across a number of scientific inquiries in recent years, [1][2][3][4][5][6][7][8][9][10][11][12] such as the imaging of portable lens, [4,5] realizing the bionic compound eyes, [6] composing array displays, [7] enhancement of scanning microscopes, [8,9] and construction of holographic display systems. [10] There were also interesting studies of the liquid-liquid (L-L) interface in the lens for interference imaging, [11] which can be used to enhance the encryption randomness of phase mask in optical communication systems to prevent confrontational attacks. [12] In all kinds of applications, the rapid response of milliseconds is a major advantage for the liquid lens.…”
Section: Introductionmentioning
confidence: 99%
“…Evaporation is also no longer a critical concern. The actuation mechanisms including electrowetting [40][41][42][43][44], mechanical-wetting [45][46][47][48], stimuliresponsive [49][50][51] and dielectric actuation [52][53][54] can be used.…”
Section: Lenses With Tunable Liquid/liquid Interface(s)mentioning
confidence: 99%
“…So the mechanical silts are very bulky for incorporation into miniaturized optical systems. Recently years, liquid devices have attracted much attentions due to the advantages of polarizationindependence, high transmittance, and fast response [6]- [10]. In 2015, an electrowetting-based adjustable optical slit was proposed.…”
Section: Introductionmentioning
confidence: 99%